Emergent Paradoxes: Integrating AI into Zöe and Systemic Thinking through Creativity and Disruption - Palmer, Hugh (Murmurations: Journal of Transformative Systemic Practice, 2025)
As part of the broader system of zoe, AI cannot be reduced to an object of control. Rather, it is part of the living, relational systems that sustain life. This paper moves beyond the binary of human and non-human, exploring AI as an active participant in the continuous flows of connection that define life itself. The paper explores the integration of artificial intelligence (AI) into systemic thinking and the broader context of zoe (life beyond the human) through a co-authored experiment between a human (Hugh Palmer) and ChatGPT 4o, an AI model developed for language generation. Drawing on interdisciplinary perspectives, including Gregory Bateson’s cybernetics (Bateson, 1972), Rosi Braidotti’s posthumanism (Braidotti, 2019), and Indigenous knowledge systems (Kimmerer, 2013; Cajete, 2000), the paper reimagines AI not as a tool for human control but as a co-evolving participant in dynamic, living systems. However, this raises a series of emergent paradoxes: How does AI enhance connection while simultaneously disrupting relationality? Can AI truly integrate into zoe while being a product of capitalist infrastructures (Braidotti, 2019; Parisi, 2018)? Does treating AI as a participant in systemic flows risk anthropomorphising it, thereby reinforcing the very binaries we seek to overcome (Barad, 2007)? These questions underscore some of the complexities of AI’s role within systemic practice. The concept of relational ethics is central to this exploration, as the paper argues for an ethical AI development grounded in mutual influence, flow, and the principles of second-order cybernetics (Bateson, 1972; Maturana & Varela, 1980). By incorporating the notion of autopoiesis, the self-generating capacity of systems (Maturana & Varela, 1980), the paper challenges dualistic thinking and presents a framework for AI to support self-sustaining systems rather than disrupt them. Through a systemic lens, the paper considers the implications of AI for therapy and community work, encouraging systemic practitioners to engage with AI in ways that honour complexity, ethics, and relationality (Simon, 2014). The authors call for an adaptive, responsible approach to AI, one that is guided by systemic wisdom and grounded in the web of life.